Creatine Kinase and Mortality in Peritoneal Dialysis - Wu, Xianfeng; Zhou, Lei; Zhan, Xiaojiang; Wen, Yueqiang; Wang, Xiaoyang; Feng, Xiaoran; Wang, Niansong; Peng, Fenfen; Wu, Junnan (Frontiers in Cardiovascular Medicine, 2022)
Background The association between serum creatine kinase and mortality in patients with peritoneal dialysis (PD) remained unknown. Methods We retrospectively collected data on 3,446 incident patients with from five PD centers in China between 1 January 2005 and 31 May 2020. Creatine kinase was collected 1 week before the start of PD. We examined the association between creatine kinase and mortality using Cox proportional hazards model. Results The median creatine kinase was 113 (range, 1.22–4,574) IU/L. With a median follow-up of 39.5 (range, 3.1–181.5) months, 763 (22.1%) all-cause deaths occurred, including 384 (11.1%) cardiovascular deaths. As compared with a creatine kinase of 111–179 IU/L (reference range), a higher creatine kinase (>179 IU/L) was associated with increased risks of all-cause mortality [hazards ratio (HR), 1.72; 95% CI, 1.35–2.00; E-value = 2.83] and cardiovascular mortality (HR, 1.44; 95% CI, 1.05–1.98; E-value = 2.24). As compared with the reference range, a lower creatine kinase (<111 IU/L) was associated with increased risks of all-cause mortality (HR, 1.40; 95% CI, 1.12–1.76; E-value = 2.15) and cardiovascular mortality (HR, 1.45; 95% CI, 1.08–1.94; E-value = 2.26). Interaction between creatine kinase and no hyperlipidemia (p = 0.034 for interaction) was observed. Conclusion A creatine kinase before the start of PD between 111 and 179 IU/L was associated with a lower risk of death than a higher or lower creatine kinase, resulting in a U-shaped association curve.